Do the fastest sperm within an ejaculate swim faster in subordinate than in dominant males of Arctic char? - Vaz Serrano, Jonathan; Folstad, Ivar; Rudolfsen, Geir; Figenschou, Lars (Canadian Journal of Zoology, 2006)
Theoretical models predict that subordinate males should have higher sperm velocity to compensate for their disadvantaged mating role and because they experience sperm competition more frequently than dominant males. Differences in mean velocity between sperm of dominants and subordinates in the predicted direction are also documented for a few species, including the Arctic char, Salvelinus alpinus (L., 1758). Yet, this difference in mean velocity does not imply that the fastest sperm within an ejaculate, which are those most likely to fertilize eggs, swim faster in subordinates than in dominants. We studied the 5% and 10% fastest sperm cells in ejaculates of dominant and subordinate Arctic char. Before individuals attained their status, there were no differences in velocity between the fastest sperm of males that later became dominant or subordinate. Yet, after establishment of social position, subordinates showed significantly higher sperm swimming speed of the fastest cells in the first 30s post activation (i.e., at 15, 20, and 30s post activation). Males that became subordinates showed no change in sperm speed of the fast cells compared with those at pre-trial levels, whereas males that became dominant reduced the speed of their sperm (15s post activation) compared with those at pre-trial levels. Our results suggest that males which attain social dominance are unable to maintain high sperm velocity, even among the small fraction of the fastest cells. D'après les modèles théoriques, les mâles subordonnés doivent posséder des spermatozoïdes plus rapides pour compenser leur position désavantageuse dans la reproduction; ils subissent aussi la compétition spermatique plus souvent que les mâles dominants. Il existe des données qui montrent des différences de vitesse moyenne dans le sens prévu entre le sperme de dominants et de subordonnés chez quelques espèces, dont l'omble chevalier, Salvelinus alpinus (L., 1758). Néanmoins, cette différence de vitesse moyenne ne veut pas dire que les spermatozoïdes les plus ...